Synthesis and cytotoxicity evaluation of 2-benzoylbenzoxazoles by Reaction of o-aminophenol with Acetophenone Catalyzed by Sulfur in DMSO - Doan, Thi Yen Oanh; Tran, Thi Yen; Nguyen, Le Anh; Ngo, Quoc Anh (JST: Engineering And Technology For Sustainable Development, 2022)
The 2-benzoylbenzoxazole derivatives were known for their significant biological activities such as anti-proliferative activity, inhibition of FAAH enzyme (fatty acid amide hydrolase). Synthesis of biologically active 2-benzoylbenzoxazole motifs often relies on a multi-step process or precursors carrying active groups. In this study, we report a simple and efficient method for the synthesis of such compounds by the direct reaction of o-aminophenol with acetophenone catalyzed by sulfur in DMSO. The reaction was found to take place via benzoxazolation in the Willgerodt rearrangement of acetophenone, followed by benzylic oxidation to restore the carbonyl functional group. With the optimized reaction conditions, we have synthesized a number of 2-benzoylbenzoxazoles 3aa - 3ae derivatives with good yield from 60 to 75%. Several synthetic derivatives have shown cancer cell growth inhibitory activity with IC50 values ranging from 36.37 to 56.08 µM. The cytotoxicity of some resulting compounds was evaluated and showed that the ellipticine positive control was stable in the experiment.